Strategi Penanganan Pascapanen Kopi Pinogu Berbasis AHP pada Faktor Dominan Penurunan Mutu di UMKM Wakapu, Desa Pinogu - Jilham, Aqshal; Lahay, Idham Halid; Uloli, Hendra (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study analyzed the factors causing the decline in the quality of Pinogu coffee using the Analytic Hierarchy Process (AHP) method, involving seven respondents from farmers and MSMEs. The analysis identified six main criteria: color irregularity, musty odor, moisture, physical damage, mass/weight, and hollow beans. Based on the AHP calculation, bean color irregularity emerged as the most dominant factor (weighting 42%), followed by musty odor and mass/weight (each 19%). A Consistency Ratio (CR) value of 0.03 (<0.1) indicates a high level of assessment consistency. These findings reveal that the main quality problems originate from the harvesting and post-harvest handling stages. The study recommends that Wakapu MSMEs prioritize improvements in the ripe fruit selection process and moisture control as strategic steps to improve quality. The study results provide a practical contribution in the form of an effective intervention priority scale for local coffee entrepreneurs with limited resources.